O imaginário sobre o sujeito professor nos documentos oficiais: entre o religioso e o jurídico, uma repetição ideológica, (não) idêntica - Linck, Ieda Márcia Donati (2015)
The present thesis was developed in discursive perspective, carried out from an investigation into the history of higher education in Brazil and teacher training. It has been a focus to understand the functioning of the official discourse on public policies for teacher training, as constitutive of discourse about the teacher subject, in particular Language, aligning this search with the compulsory supervised internship practice for obtaining the Teacher s Degree. The starting point of the research is materialized in the organizational documents of the Language Course at the University Of Cruz Alta/RS. The guiding theme is in the nomination clipping guardian, the definition given to the degree in Language. The theoretical device was established by discourse theory, taking as reference for the analysis, the French line, pecheuxtian in its articulation with the History of Linguistic Ideas (HLI). We try to answer: How was the discourse about the teacher subject? How the meaning effects production happens, in the relationship of the official discourse with the institutional discourse and religious?; Is the discursive paraphrastic process constitutive of the discourse about the teacher? For this study we set the following objectives: 1) Understanding the constitution of the discourse about the teacher subject, evidenced in the juridical and institutional documents, among which the Laws of Directives and Bases of National Education, from an ideological repetition (not) identical ; 2) Analyze the discursive movement of paraphrase by religious discourse, as the constitutive imaginary functioning about the Portuguese teacher subject. The analysis file has been set up in several juridical documents, which meant discourse analysis of the functioning of discourse about, in the LDBS (Law Nº. 4024 / 1961; 5540/1968 and 9394/1996). During the entire process of observation, made in the essential documents to the thesis, it did not think about the predominance of a theoretical sense to the analytical. Otherwise, what we try to bring out was the merger between the two assessments. We were realizing the need for interaction and confrontation of these actions on a survey, which poses to analyze the discourse about. Still, as a form of organization, this thesis is divided into two parts (I. Construction of the route, and II. The materialization of discourse about) and five chapters, namely: 1) To read the file: When language and history (dis) encounter; 2) Establishing relationships: the constitution of the Portuguese language as a teaching object to the teacher training in Brazil; 3) Conditions of production and materialization of power in official discourse: the laws of education directives and bases; 4) Analytical Device: (re) explaining a gesture of reading and the look of the analyst; 5) paraphrastic process as polysemic process: to beyond the official discourse, the religious discourse. The first three chapters constitute the theoretical device, already with an analytical bias; the latter two bring the analytical device, where we present our analysis as well as sustain the results that we present in the considerations (not) finals. In the fifth chapter, the thesis confirms itself: the paraphrastic process, a non-identical ideological repetition, is constitutive of the discourse about the teacher subject, materialized by the official discourse, which intersects with the religious discourse. Our reflection leads us to the understanding that the official discourse combines a network of relationships with science, education, society and religion, as production conditions. This link establishes itself, including with the compliance of the compulsory supervised internship, described as legitimizing practice to the degree. This discourse, as an ideological movement, is being reproduced by the segments that make up society. In it, the discourse about the teacher has firmed its identification as a missionary, a devoted, restricting its professionalism. In addition, we evidenced that the discussion about the laws that govern the education in the country deserves a wider space in teacher training courses.